2015
DOI: 10.1055/s-0035-1562939
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Bilateral Bullectomy for Simultaneously Developed Bilateral Primary Spontaneous Pneumothorax: Ipsilateral Transmediastinal versus Bilateral Sequential Approach

Abstract: Simultaneously developed bilateral primary spontaneous pneumothorax (BPSP) is an indication for thoracic surgery of both sides. Recently, we have reported a new technique for BPSP, which is ipsilateral apicoposterior transmediastinal (TM) bullectomy of both sides using video-assisted thoracoscopic surgery (VATS), and we compared this TM VATS with bilateral sequential (BS) VATS for BPSP. From June 2003 to May 2014, 11 and 14 patients were performed VATS TM and BS bullectomy for BPSP, respectively. We reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Lee et al performed bilateral VATS in 13 patients with SBPSP and reported 2 (7.7%) recurrence episodes [12]. However, the study by Cho et al, which reported the most cases of SBPSP, found the recurrence rate to be as high as 44% [7]. In this study, Cho et al performed ipsilateral transmediastinal approach VATS in approximately half of the patients and traditional bilateral sequential approach in the other half.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Lee et al performed bilateral VATS in 13 patients with SBPSP and reported 2 (7.7%) recurrence episodes [12]. However, the study by Cho et al, which reported the most cases of SBPSP, found the recurrence rate to be as high as 44% [7]. In this study, Cho et al performed ipsilateral transmediastinal approach VATS in approximately half of the patients and traditional bilateral sequential approach in the other half.…”
Section: Discussionmentioning
confidence: 80%
“…For patients who underwent bilateral VATS, the overall recurrence rate was 27.3%. However, it is important to note that the number is largely influenced by one relatively large study by Cho et al that showed the recurrence rate of 44% [7]. All included studies are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%